Copy number variant analysis and genome-wide association study identify loci with large effect for vesicoureteral reflux - Verbitsky, Miguel; Krithivasan, Priya; Batourina, Ekaterina; Khan, Atlas; Graham, Sarah E.; Marasà, Maddalena; Kim, Hyunwoo; Lim, Tze Y.; Weng, Patricia L.; Sánchez-Rodríguez, Elena; Mitrotti, Adele; Ahram, Dina F.; et al. (Journal of the American Society of Nephrology, 2021)
Background: Vesicoureteral reflux (VUR) is a common, familial genitourinary disorder, and a major cause of pediatric urinary tract infection (UTI) and kidney failure. The genetic basis of VUR is not well understood. Methods: A diagnostic analysis sought rare, pathogenic copy number variant (CNV) disorders among 1737 patients with VUR. A GWAS was performed in 1395 patients and 5366 controls, of European ancestry.Results: Altogether, 3% of VUR patients harbored an undiagnosed rare CNV disorder, such as the 1q21.1, 16p11.2, 22q11.21, and triple X syndromes ((OR, 3.12; 95% CI, 2.10 to 4.54; P=6.35×10−8) The GWAS identified three study-wide significant and five suggestive loci with large effects (ORs, 1.41–6.9), containing canonical developmental genes expressed in the developing urinary tract (WDPCP, OTX1, BMP5, VANGL1, and WNT5A). In particular, 3.3% of VUR patients were homozygous for an intronic variant in WDPCP (rs13013890; OR, 3.65; 95% CI, 2.39 to 5.56; P=1.86×10–9). This locus was associated with multiple genitourinary phenotypes in the UK Biobank and eMERGE studies. Analysis of Wnt5a mutant mice confirmed the role of Wnt5a signaling in bladder and ureteric morphogenesis. Conclusions: These data demonstrate the genetic heterogeneity of VUR. Altogether, 6% of patients with VUR harbored a rare CNV or a common variant genotype conferring an OR >3. Identification of these genetic risk factors has multiple implications for clinical care and for analysis of outcomes in VUR.
Gesehen am 16.12.2021